Sosialisasi Pemanfaatan DBHCHT untuk Kesejahteraan Masyarakat melalui Siaran Kebumen TV - Dicky Satria Ramadhan; Istiqomah Istiqomah; Eka Setya Ramadhan; Asyifa Nur Laeli Munawaroh; Enos Adryansyah Gumilang (Yumary: Jurnal Pengabdian kepada Masyarakat, 2026)
Purpose: This community service program aims to enhance public awareness of the strategic contribution of the Tobacco Excise Revenue Sharing Fund (DBHCHT) to regional economic development and community welfare. The activity also responds to persistent challenges in DBHCHT management, including issues of transparency, effectiveness, and governance in regions affected by the circulation of illegal cigarettes. Research Methodology: The program was delivered through a live talk show on Kebumen TV in collaboration with the local government and the Customs and Excise Office. The session was attended live by 30 participants and subsequently disseminated through YouTube and Kebumen TV rebroadcasts, allowing broader reach and sustained access. Results: The socialization indicated that although DBHCHT carries substantial potential to support welfare enhancement, public health services, labour empowerment, and law-enforcement initiatives, its implementation remains suboptimal. Key constraints include limited transparency in fund allocation, inadequate community involvement, low absorption capacity, and persistent issues linked to illegal cigarette circulation. Conclusions: Strengthening governance, increasing public literacy, and fostering multi-stakeholder collaboration are crucial to optimizing DBHCHT utilization. Limitations: The television broadcast format limits real-time monitoring of participants’ understanding, engagement level, and feedback, thereby constraining the depth of evaluation that can be conducted. Contributions: This activity provides the public with a clearer understanding of DBHCHT’s strategic role, promotes a transparent and participatory model of fund management, and encourages active collaboration to maximize DBHCHT’s impact on regional economic development and community welfare.